Controlling diffusion in sol-gel derived monoliths - Kanungo, Mandakini (Langmuir : the ACS journal of surfaces and colloids, 2005)
Redox probes were trapped within a silica monolith prepared in part with organoalkoxysilanes containing a quaternary ammonium functional group. The diffusion coefficients of the entrapped molecules were measured as the gels were slowly dried using chronoamperometry and cyclic voltammetry with ultramicroelectrodes. Gel-entrapped cobalt(II) tris(bipyridine) (Co(bpy)(3)(2+)) diffuses at rates similar to that measured in the sols by incorporating a small amount of the positively charged functional group in the matrix. In comparison, the diffusion coefficient of gel-entrapped ferricyanide (Fe(CN)(6)(3-)) drops an order of magnitude relative to its value in the sol soon after gelation. These results demonstrate the ease at which diffusion in hydrated gels can be easily controlled by simply changing the charge on the walls of the silica host